Sosialisasi Resiko Non Klinis Pernikahan Usia Anak di SMAN I Gerung - Eneng Garnika; Dewi Rayani; Lu’luin Najwa; Diah Lukitasari (Jurnal Pengabdian UNDIKMA, 2021)
This community service activity aims to provide knowledge in child marriage which can cause bad risks, so it is necessary to do prevention by delaying the age of marriage, continuing studies and planning life to be able to carry it out better. Given the appeal from the government not to carry out activities that involve many people, this service program is carried out through socialization in limited classes to be able to maintain the Health protocol with a number of participants less than 20 pesetas. The steps in the implementation of this service include: (1) Providing gradual education to students about the non-clinical risks of child marriage and its prevention; Non-clinical risks of child marriage; planning for the future and further studies, and the importance of education to continue a better life. (2) Conduct a question and answer session at the end of the delivery of socialization materials. (3) Evaluation of child marriage risk socialization program activities and program sustainability plans. The result of this community service activity is that students understand the non-clinical risks of child marriage and can plan for the future, by continuing their studies or by doing entrepreneurship.